Hanehalki gelir ve tüketim harcamalari anket sonuçlari = . Household income and consumption expenditures survey results (Devlet Istatistik Enstitüsü, 1982)
Also titled: Household income and consumption expenditures survey results. 1978-1979 Samsun.